Avaliação de risco relativo para tuberculose bovina em municípios do Estado do Espírito Santo a partir de dados de matadouros - Paoli, Talita Maria Pimenta de (2013)
Bovine tuberculosis is a chronic bacterial disease caused by Mycobacterium bovis, which affects humans and animals. It’s an important zoonosis and also causes economic losses in the production of meat and milk. By the time the prevalence and regional distribution of tuberculosis are not well characterized for the Brazilian territory and this knowledge is fundamental to the control of this disease. For these reasons, attempted to estimate the prevalence and determine the risk of bovine tuberculosis in cattle coming from different regions of Espírito Santo State based on the findings of lesionsof tuberculosis in cattle slaughtered in state from January 2009 to December 2012. Statistic data analysis revealed that the the prevalence of bovine tuberculosis in cattle of the Espírito Santo State was 0.23% and cattle of D region have relative risk to presents tuberculosis 11.36, 7.07 and 1.7 higher than the regions A, B and C respectively . The municipal district of Muqui had the highest prevalence (1%) and relative risk for bovine tuberculosis up to 19.6 times higher when compared to other counties in the region D. These results indicate the need for preparation and adoption of measures to control tuberculosis in the state, especially in the region with the highest prevalence.